Tradisi Anjang Sana-Sini Sebagai Bentuk Kerukunan Antar Umat Beragama di Desa Besowo - Syaepu, Indra Latif (IAIN Kediri, 2019)
This paper sheds light on interreligious harmony taking place in the Village of Besowo where the so-called Anjang Sani-Sini tradition plays a significant role. The adaptation and integration between religion and local cultures have transformed new values in a given society. Likewise, the Anjana Sana-Sini tradition is a transformative form of an alledgedly exclusive religious doctrine within a pluralistic culture so as to bring up new ethical values or traditions. The Anjang Sana-Sini tradition is a tradition of mutual visits carried out by the residents of Besowo regardless of their religious backgrounds. The article showed that this tradition hassuccesfully fostered kinship and interreligious harmony among the people. In addition, this tradition has also created a social resilience to the threat of conflicts and at the same time estabslihed interreligious harmony in the village.Keywords: Anjang Sana-Sini, Local Culture, Interreligious Harmony